A Reconsideration of the Stiglitz-Weiss Model with a Discrete Number of Borrower Types - Susanne Steger; Helke Waelde (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
In this paper we show that the equilibrium in the Stiglitz-Weiss model (Stiglitz and Weiss, 1981) is a two-interest rate equilibrium. For this we use the true return-function for banks shown by Arnold (2005), the assumption of Bertrand competition and make a consideration for a discrete number of borrowers. Rationing only affects one group of the borrowers, i.e. the borrowers with a safe project. The risky group always receives the funds it demands.
Keywords: D82; E51; G21; 330; credit rationing; asymmetric information; adverse selection